Arquitetura logística baseada em modelos: uma contribuição a gestão estratégica da logística terceirizada - Teixeira, Tânia Regina Brasileiro Azevedo (2003)
The thesis identifies the essential dimensions of the management of third party logistics through the study of the outsourcing process of the logistics activities of a large Brazilian wholesale distributor. The author has developed a tool capable of orienting and guiding logistics providers to structure their management systems in three aspects: (1) fulfilling the client's requirements, (2) analyzing logistics and tributary configurations and (3) obtaining the necessary information to determine and manage the service levei rendered to the client. Therefore the author proposes a set of conceptual management models, which shall simplify the management and transform the logistical system of the provider into a strategic capacity, improving its competitiveness.